Ultraviolet–visible light photoluminescence induced by stacking faults in 3C–SiC nanowires. (25th March 2019) - Yu, Hailing; Wang, Qiang; Yang, Lei; Dai, Bing; Zhu, Jiaqi; Han, Jeicai
Abstract: The relationship between stacking faults and optical properties in 3C–SiC nanowires is reported in this paper. 3C–SiC nanowires prepared at 900 °C have high density stacking faults. The stacking faults cause a change in the Si–C atom stacking sequence and form nanosegments of 4H–SiC and 6H–SiC in the 3C–SiC matrix. The mixture of polytypes leads to a shift in the peaks and the addition of peaks in both Raman spectra and photoluminescence (PL) spectra. The Raman peaks are centered at 785 cm −1 and at 935 cm −1 and correspond to the transverse optic mode and the longitudinal optic mode of 3C–SiC, respectively. The PL peaks are blueshifted and the emissions are in the ultraviolet–visible light band.